Strengthening the Business Judgment Rule in Indonesia: Lessons from Malaysia - Jatna, R. Narendra; Amir Firmansyah; Hasbullah; Muhammad Umar Bin Abdul Razak (Lembaga Contrarius Indonesia, 2025)
The Business Judgment Rule (BJR) serves as a fundamental doctrine in corporate law, protecting company directors from personal liability when they act in good faith, exercise due diligence, and avoid conflicts of interest. However its recognized importance in safeguarding directors’ discretion, Indonesian lawmakers and courts have not fully developed its application, as shown by limited statutory codification, inconsistent judicial interpretation, and insufficient empirical analysis, thereby hindering coherent corporate governance and generating uncertainty in directors’ decision-making authority. This study analyzes the implementation of the BJR in Indonesia through a comparative lens with Malaysia. Using a normative and comparative legal approach, the research reveals that Indonesia’s current framework lacks clarity, comprehensive codification, and consistent judicial interpretation particularly in the private sector. The research findings demonstrate that, first, the implementation of the Business Judgment Rule (BJR) in Indonesia remains constrained by procedural ambiguity, which undermines consistent and predictable enforcement. Second, the allocation of the burden of proof lacks clarity, thereby weakening both the protection afforded to directors and the reliability of judicial determinations. Third, institutional support for the practical application of the BJR is insufficient, limiting its capacity to promote effective corporate governance. In response, the study recommends comprehensive reform of the Indonesian Company Law, the incorporation of safe-harbor provisions, the enhancement of judicial competence through specialized training, and the reinforcement of corporate governance mechanisms to improve legal certainty and strengthen directors’ accountability. Advancing the BJR framework is essential to encourage innovation, reduce legal risks, and enhance the competitiveness and resilience of Indonesia’s corporate sector.